Modernitas dan Keindonesiaan Fatwa Majelis Ulama Indonesia - Muhammad Yusuf (JURNAL INDO-ISLAMIKA, 2016)
This research shows that 19 (nineteen) fatwas of 104 (one hundred and four) fatwas of the Indonesian Ulama Council (MUI) from 1983 to 2009 are reflecting modernity and the Indonesia-ness. The modernity of the fatwas is implemented in the using of maqasid shari‘ah, the maslahat principle, collective ijtihad, and flexibility in madhhab. As for the Indonesianess of the fatwas is implemented at the local wisdom which includes the consideration of: National Stability of Indonesia, the Republic of Indonesia (NKRI), Public Order, National Culture, and Legislation regulated in Indonesia.The research supports the thought of the contextualist group which is represented by Sahal Mahfudh, Ali Yafie and Munawar Chalil; both of them echo the contextual relationship between fiqh and the aspects of Indonesian people’s life. Also Muhammad Atho Mudzhar which states that the implementation of any Islamic law is the result of interaction between the jurist or mufti with his sociocultural and sociopolitical environment. Musfirin al-Qahtani as well states the importance of istinbat methodology in facing the development of the contemporary Islamic law (fiqh) by standing on the shariah arguments, the fiqh formulas (qaidah fiqhiyyah), takhrij, and maqasid al-shari‘ah.